Nilai-nilai Moral dalam Novel Jermal Karya Yokie Aditiyo - Silvia, Roza; Abdurahman, Abdurahman; Basri, Irfani (Universitas Negeri Padang, 2013)
The purpose of this study was (1) to describe the moral conscience, (2) describe the moral values ​​of freedom and responsibility, (3) describe the value of moral rights and obligations, (4) describe the moral value ​​and norm. The data of this study are sentences that describe moral values​​. The data source of this research is the novel Jermal by Yokie Adityo first printed work was published in Yogyakarta by publisher Landscape Library in 2009 with the numbers as much as 138 pages ISBN 978-979-1227-75-9. This research is a qualitative descriptive method. The findings of this study consisted of 13 moral conscience, 11 moral values ​​of freedom and responsibility, 23 the value of moral rights and obligations, and 31 moral values ​​and norms.